Dietitians and Nutritionists: Stigma in the Context of Obesity. A Systematic Review. - Franziska U C E Jung; Claudia Luck-Sikorski; Nina Wiemers; Steffi G Riedel-Heller (PLoS ONE)
Aim Negative attitudes towards people with obesity are common even in health care settings. So far, the attitudes and causal beliefs of dietitians and nutritionists have not been investigated systematically. The aim of this article was to review the current state of quantitative research on weight-related stigma by dietitians and nutritionists. Method A systematic literature review was conducted in 2014 using PubMed, PsycINFO, Web of Science and Cochrane Library. Results Eight studies were found that differ in regard to study characteristics, instruments and the origin of the sample. Six out of eight studies reported weight stigma expressed by dietitians and nutritionists. Their believed causes of obesity indicated a defined preference for internal factors rather than genetics or biology. Discussion Results of studies were not homogenous. The degree of negative attitudes by dietitians and nutritionists towards people with obesity appeared to be slightly less pronounced compared to the general public and other health care professionals. Stigma and its consequences should be included into educational programs to optimally prepare dietitians and nutritionists.